PREFERENSI KONSUMEN SAGU DI KOTA KENDARI - Helviani Helviani; Sitti Aida Adha Taridala; Azhar Bafadal; Budiyanto Budiyanto (Jurnal Sosio Agribisnis, 2018)
Sago is a potential source of food with high calories and carbohydrates (rice equivalent). Sago consumer preferences can provide important information in making marketing strategy sago, and also is one of the indicators of market demand for the products of sago. The purpose of this study were to understand the srage of the purchase decision process undertaken by consumers of sago; analyze the level of customer satisfaction with sago attributes associated from sago; and analyze the consumer preference for various atrributes inherent in sago. The study was conducted in Kendari, Southeast Sulawesi Province. Respondents were all members of a population of 21 respondents consisting of 15 restaurant owners who provide meals made from sago and 6 owners agro-industry made from raw sago. The study used Engel Model Analysis, Costumer Satisfaction Index (CSI) Analysis, and Conjoint Analysis. The results of the analysis gives an overview of some consumer behavior based on the decision-making process shows that the benefits sought in the purchase buy sago sago is as a raw material to be processed into a menu of traditional food and traditional cakes Kendari. Color sago is the main thing, which will be seen and considered by consumers to make purchases between and will buy sago in traditional markets as close to the place of business. The level of consumer satisfaction in this study were satisfied with the preference category that consumers like sago with normal color (pure white), normal scent (odorless), low prices and package sizes are 20 kg. The resulting combination of sago four attributes (color, flavor, price and package sizes) is acceptable to describe consumers' desire sago in Kendari. Keywords: consumer behavior; sago; Engel Model; Customer Satisfaction Index (CSI); conjoint analysis